Tropes As A Means Of Artistic Expressiveness In The Idiolect Of M.Bulgakov (Czech Journal of Multidisciplinary Innovations, 2025)
The article examines the system of tropes as one of the essential components of the artistic-expressive means of the Russian language, which are characteristic of M. Bulgakov’s idiolect